2011
DOI: 10.1002/for.1235
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Survey‐Based Inflation Forecasts

Abstract: This paper first shows that survey-based expectations (SBE) outperform standard time series models in US quarterly inflation out-of-sample prediction and that the term structure of survey-based inflation forecasts has predictive power over the path of future inflation changes. It then proposes some empirical explanations for the forecasting success of survey-based inflation expectations. We show that SBE pool a large amount of heterogeneous information on inflation expectations and react more flexibly and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A variety of studies has found survey expectations of future inflation useful for constructing inflation forecasts, see for example Ang et al (2007) and Gil-Alana et al (2011). In evaluating the accuracy of survey expectations of inflation, Grant and Thomas (1999) argue that cointegration between survey responses and realized inflation is a weak requirement of rationality and find support for this hypothesis.…”
mentioning
confidence: 99%
“…A variety of studies has found survey expectations of future inflation useful for constructing inflation forecasts, see for example Ang et al (2007) and Gil-Alana et al (2011). In evaluating the accuracy of survey expectations of inflation, Grant and Thomas (1999) argue that cointegration between survey responses and realized inflation is a weak requirement of rationality and find support for this hypothesis.…”
mentioning
confidence: 99%
“…Equations and imply this idea, as the household updates the coefficient parameter based on the difference between its previous period's forecast and the experts' outlook on future price developments. Gil‐Alana, Moreno, and Pérez de Gracia () in fact show that survey‐based professional expectations outperform different time series models in out‐of‐sample prediction of inflation. As a measure for professional forecasts, we use monthly figures of inflation expectations for the current and the following year published by Consensus Economics.…”
Section: Different Learning Rulesmentioning
confidence: 97%
“…27 Another difference between between my work and the studies of Stock and Watson (2007), Cogley and Sargent (2005b) and Cogley et al (2010) is to condition inflation forecasts on survey data. A variety of studies has found survey expectations of future inflation useful for constructing inflation forecasts, see for example Ang et al (2007) and Gil-Alana et al (2011). In evaluating the accuracy of survey expectations of inflation, Grant and Thomas (1999) argue that cointegration between survey responses and realized inflation is a weak requirement of rationality and find support for this hypothesis.…”
Section: Related Literaturementioning
confidence: 99%